If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -75 + -6x = 7x + 21 Reorder the terms: -75 + -6x = 21 + 7x Solving -75 + -6x = 21 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -75 + -6x + -7x = 21 + 7x + -7x Combine like terms: -6x + -7x = -13x -75 + -13x = 21 + 7x + -7x Combine like terms: 7x + -7x = 0 -75 + -13x = 21 + 0 -75 + -13x = 21 Add '75' to each side of the equation. -75 + 75 + -13x = 21 + 75 Combine like terms: -75 + 75 = 0 0 + -13x = 21 + 75 -13x = 21 + 75 Combine like terms: 21 + 75 = 96 -13x = 96 Divide each side by '-13'. x = -7.384615385 Simplifying x = -7.384615385
| 3w=732 | | x^2+34x+94= | | 6x+7=143-9x | | 9x-16=6x-2 | | x-21=7 | | 4x^2=-5 | | -258=m-587 | | x^2-2x+7=7 | | 25+4m=2m+65 | | 68-7x=20x+20 | | x+26=45 | | 8-9x=88-37x | | s-904=-615 | | 8-9x=88-27x | | x-26=45 | | 2x+27=5x-9 | | s-2=31 | | 8(3n-2)=(6n+2)+4 | | -18-4x=6-8x | | 174-4x=23x+18 | | 8a+5a+5b-3b= | | 2x+20=9x-27 | | -16=0.2n | | 3/5=6 | | 122-3x=15x+24 | | 5(3x+1)=4x-8x | | 1+4m+5m^2+2m^3=0 | | 1-3+7=6 | | 5u-10v= | | 12-9x=35-16x | | x^3-9x^2+24x+1=0 | | 4+3*5=x |